2009
DOI: 10.1007/s11229-009-9578-9
|View full text |Cite
|
Sign up to set email alerts
|

On having no reason: dogmatism and Bayesian confirmation

Abstract: Recently in epistemology a number of authors have mounted Bayesian objections to dogmatism. These objections depend on a Bayesian principle of evidential confirmation: Evidence E confirms hypothesis H just in case Pr(H|E) > Pr(H). I argue using Keynes' and Knight's distinction between risk and uncertainty that the Bayesian principle fails to accommodate the intuitive notion of having no reason to believe. Consider as an example an unfamiliar card game: at first, since you're unfamiliar with the game, you assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…See, e.g., (Brogaard, 2013), (Brown, 2013), (Cohen, 2010), (Cullison, 2010), (Huemer, 2006 and, (Jehle 5 and Weatherson, 2012), (Kung, 2010), (Lycan, 2013), (Moretti, 2015), (Pollock and Cruz, 1999), (Pryor, 2000 and, (Silins, 2008), (Tucker, 2010 and, (Weatherson, 2007), and (Wedgwood, 2013), among many others. Note that while anti-Cartesianism is often coupled with a Moorean reply to the skeptic, this is not something I build in to the view.…”
Section: !mentioning
confidence: 99%
See 1 more Smart Citation
“…See, e.g., (Brogaard, 2013), (Brown, 2013), (Cohen, 2010), (Cullison, 2010), (Huemer, 2006 and, (Jehle 5 and Weatherson, 2012), (Kung, 2010), (Lycan, 2013), (Moretti, 2015), (Pollock and Cruz, 1999), (Pryor, 2000 and, (Silins, 2008), (Tucker, 2010 and, (Weatherson, 2007), and (Wedgwood, 2013), among many others. Note that while anti-Cartesianism is often coupled with a Moorean reply to the skeptic, this is not something I build in to the view.…”
Section: !mentioning
confidence: 99%
“…25 E.g., (Vogel, 2014). 26 E.g., (Cohen, 2010), (Jehle and Weatherson, 2012), (Kung, 2010), (Moretti, 2015), (Pryor, MS and 2013), 27 (Vogel, 2014), and (Weatherson, 2007).…”
Section: First Option: Biting the Bulletmentioning
confidence: 99%
“…White's objections have impressed many epistemologists and led some to respond. For instance, Pryor (manuscript), Weatherson (2007) and Kung (2010) all suggest ways to revise the Bayesian framework to accommodate the intuitions of the dogmatist. 15 In contrast with revisionary responses of this type, Silins (2007) argues that White hasn't actually shown that DG and Bayesianism are incompatible.…”
Section: Dogmatism and Bayesianism Are Not Inconsistentmentioning
confidence: 99%
“…26 For example, Pryor (manuscript) states that the situations in which dogmatism is meant to apply to respond to the perceptual sceptic -so, presumably, the typical situations adduced by the perceptual sceptic -are those in which the epistemic subjects can conceive of some non-perceiving alternative sh 'but are wholly uninformed about it' (5, my emphasis). Kung (2010) describes the same situations as those in which 'the subject has no [default] reason to believe any skeptical alternative…”
Section: Dogmatism and Bayesianism Are Not Inconsistentmentioning
confidence: 99%
“…For example, a dogmatist might argue that justification to have a low credence in the proposition I'm not being deceived has far more devastating consequences when it is risky than uncertain, when it is based on evidence than ignorance. Kung's (2010) attempt to exploit the distinction between risk and uncertainty is especially modest, because, like the approach in the previous sub-section, it can assume the classical Bayesian formalism for the sake of argument. His goal is to explain how, from within the classical Bayesian framework, one might try to model the difference between risk and uncertainty in a way that a dogmatist will find appealing.…”
Section: Strategy 2: Distinguish Risk and Uncertaintymentioning
confidence: 99%